Understanding ecosystem responses to recurrent marine heatwaves - Emily Lester; Stanley Mastrantonis; Sharyn M. Hickey; Anna Lafratta; Jessica A. Benthuysen; Eben Afrifa-Yamoah; Arani Chandrapavan; Martial Depczynski; Richard D. Evans; David V. Fairclough; Christopher J. Fulton; Marthe Monique Gagnon; et al. (Biological Conservation, 2026)

Wuthuga (dugong) population status in Gathaagudu (Shark Bay) sea country - Holly Raudino; Amanda Hodgson; Chris Cleguer; Kym Reeve; Molly Moustaka; Osmar Luiz; Simone Strydom; Kathy Murray; Neilisha Oakley; Tariq McDonald; Abby Leyendekkers; Jay Hayes; et al. (Frontiers in Marine Science, 2026)
Introduction Monitoring trends in wildlife populations and their response to pressures is integral but challenging for conservation managers. Wuthuga (dugongs (Dugong dugon)) are increasingly vulnerable as extreme climatic events, such as marine heatwaves and flooding, intensify with a warming climate and increasingly impact the seagrass they are dependent upon. Methods This study estimated wuthuga abundance using two methodologies: conventional observer aerial surveys, as part of a time-series of surveys, alongside aerial imagery, in Gathaagudu (Shark Bay), Western Australia in 2023. We compare the contemporary abundance estimates with long term monitoring data (1989 – 2018) to identify temporal trends in abundance and distribution. Results Over time the observer-derived estimates of wuthuga in Gathaaguda has ranged from the highest estimate in 1999 of 13929 (± SE 1652) to the lowest in 2023 of 8688 (± SE 1119). The wuthuga population has remained stable over time, with no statistical difference discernable when density is modelled. Methods were compared for the area of highest wuthuga density in 2023 (survey block 4), the observer-derived wuthuga abundance estimate was 4551 (± SE 926) and the image-derived estimate 5748 (± SE 1765). The abundance estimates yielded from both methodologies were not statistically different. For both approaches, abundance estimates were modelled using standard approaches to account for perception and availability bias. Of all wuthuga sighted in Gathaagudu in 2023, ~9.6% were calves, which is within the range of calf proportions found in past surveys. Discussion Due to wuthuga reproductive biology, the proportion of calves observed during aerial surveys may be a useful secondary indicator of population condition and seagrass availability preceding the survey. The proportion of calves observed in 2023 is an encouraging indicator of population condition. The relative stability and size of the Gathaagudu wuthuga population highlights its global importance to the persistence of the species.

Sediment burial negatively impacts the growth of seagrass Posidonia sinuosa - Chanelle Webster; Nicole Said; Natasha Dunham; Simone Strydom; Kathryn McMahon (Marine Pollution Bulletin, 2025)

Global Patterns and Drivers of Seagrass Biomass, Net Primary Production and Meadow Structure - Nicole R. Foster; Enric Gomis; Diana I. Montemayor; Simone Strydom; Miguel Angel Mateo; Eduard Serrano; Aurora M. Ricart; Martin Dahl; Ines Mazarrasa; Paulina Cisternas; Harry Whiteley; Elliott J. Bates; et al. (Journal of Biogeography, 2025)
Aim We decipher global patterns in seagrass growth and structure to advance seagrass science, facilitate multidisciplinary research, and promote effective management strategies and policy development for seagrass habitats. Location: Global. Time period: 1975 to 2024. Major taxa studied: Seagrasses—marine angiosperms. Methods A global data set on seagrass total biomass, total net primary productivity (NPP), shoot density, and percent cover was compiled across 11 genera. We tested how these variables change across seagrass genera, life‐history strategy, and geographic location; and then modelled the environmental drivers (temperature, nutrients, light availability) of the patterns observed. Results The mean (±SE) total biomass of seagrasses globally was estimated at 340 ± 10 g DW m −2 and total NPP was estimated at 5.4 ± 0.4 g DW m −2 d −1 . Mean shoot density across all genera was 1,780 ± 67 shoots m −2 and percent cover was 42% ± 1%. Persistent genera showed the highest total biomass followed by opportunistic then colonising genera, whereas shoot density was higher for colonising than persistent, which had the highest percent cover. Latitudinal and bioregional patterns were identified for some genera and were mostly driven by genus‐specific traits, followed by localised environmental factors. Main Conclusions Trends in seagrass meadow ecology were largely influenced by seagrass genera and their life‐history strategy, with localised environmental factors, such as temperature and nutrients, also playing a role. Global estimates of seagrass biomass and NPP were 2‐times higher than previously reported. Seagrass life‐history strategies modulate the trade‐offs between NPP and biomass to thrive in specific habitats. This study provides the most updated global synthesis of patterns in seagrass growth and structure.

The Ability of Ruppia polycarpa to Regenerate from Seed Depends on Seasonal Porewater Salinity Dynamics and Declining Winter Rainfall Could Delay Recruitment - Chanelle L. Webster; Paul S. Lavery; Simone Strydom; Jessica Billinghurst; Kathryn McMahon (Estuaries and Coasts, 2023)
For many plants, regeneration from seed is vital for population recovery. Climate change is modifying the global hydrological cycle and a primary factor controlling germination of marine plants: salinity. How altered salinity regimes, and especially altered porewater salinity regimes, will regulate early life history stages of estuarine seagrasses is poorly understood. Here, we quantified the porewater salinity dynamics in two ephemeral estuaries that are dominated by the cosmopolitan genus Ruppia . Seedbank, germlings (germinated seeds) and seedlings were found in salinities ranging from 5 to 110 over an annual cycle. To understand the germination ecology of the dominant species, Ruppia polycarpa , seeds were exposed to treatments simulating current salinity regimes and those predicted under climate change. Seeds underwent a Dormancy treatment (15, 60, 150) followed by a Germination treatment (10, 20, 80). Generally, early life history stages were positively affected by hypersaline dormancy conditions if the subsequent Germination salinity was ≤ 20. Germination success was significantly higher for seeds transferred to 10 (65%) compared to 20 (49%) whilst no seeds germinated in 80 highlighting the risk of lower germination as estuaries become drier and more hypersaline with declining winter rainfall. However, germlings were found in situ in salinities ≥ 80 suggesting aspects of the salinity dynamics, not captured by our experimental conditions, may broaden tolerances. Dormant seeds were continuously present in situ and seedlings were observed throughout the whole of the growing season. These results are indicative of bet-hedging strategies. Future research should explore the capacity of these strategies to afford resilience to R. polycarpa to salinity variability under climate change.

Too hot to handle: Unprecedented seagrass death driven by marine heatwave in a World Heritage Area - Simone Strydom; Kathy Murray; Shaun Wilson; Bart Huntley; Michael Rule; Michael Heithaus; Cindy Bessey; Gary A. Kendrick; Derek Burkholder; Matthew W. Fraser; Katherine Zdunic (Global Change Biology, 2020)
The increased occurrence of extreme climate events, such as marine heatwaves (MHWs), has resulted in substantial ecological impacts worldwide. To date, metrics of thermal stress within marine systems have focussed on coral communities, and less is known about measuring stress relevant to other primary producers, such as seagrasses. An extreme MHW occurred across the Western Australian coastline in the austral summer of 2010–2011, exposing marine communities to summer seawater temperatures 2–5°C warmer than average. Using a combination of satellite imagery and in situ assessments, we provide detailed maps of seagrass coverage across the entire Shark Bay World Heritage Area (ca. 13,000 km 2 ) before (2002 and 2010) and after the MHW (2014 and 2016). Our temporal analysis of these maps documents the single largest loss in dense seagrass extent globally (1,310 km 2 ) following an acute disturbance. Total change in seagrass extent was spatially heterogeneous, with the most extensive declines occurring in the Western Gulf, Wooramel Bank and Faure Sill. Spatial variation in seagrass loss was best explained by a model that included an interaction between two heat stress metrics, the most substantial loss occurring when degree heating weeks (DHWm) was ≥10 and the number of days exposed to extreme sea surface temperature during the MHW (DaysOver) was ≥94. Ground truthing at 622 points indicated that change in seagrass cover was predominantly due to loss of Amphibolis antarctica rather than Posidonia australis , the other prominent seagrass at Shark Bay. As seawater temperatures continue to rise and the incidence of MHWs increase globally, this work will provide a basis for identifying areas of meadow degradation, or stability and recovery, and potential areas of resilience.

A Systematic Review of How Multiple Stressors From an Extreme Event Drove Ecosystem-Wide Loss of Resilience in an Iconic Seagrass Community - Gary A. Kendrick; Robert J. Nowicki; Ylva S. Olsen; Simone Strydom; Matthew W. Fraser; Elizabeth A. Sinclair; John Statton; Renae K. Hovey; Jordan A. Thomson; Derek A. Burkholder; Kathryn M. McMahon; Kieryn Kilminster; et al. (Frontiers in Marine Science, 2019)